2017
DOI: 10.1039/c7nr04241h
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-loaded γ-polyglutamic acid nanogels as a platform for photoacoustic imaging-guided tumor photothermal therapy

Abstract: We report the facile synthesis of polyaniline (PANI)-loaded γ-polyglutamic acid (γ-PGA) nanogels (NGs) for photoacoustic (PA) imaging-guided photothermal therapy (PTT) of tumors. In this work, γ-PGA NGs were first formed via a double emulsion approach, followed by crosslinking with cystamine dihydrochloride (Cys) via 1-ethyl-3-[3-dimethylaminopropyl]carbodiimide hydrochloride coupling chemistry. The formed γ-PGA/Cys NGs were employed as a nanoreactor to load aniline monomers via an electrostatic interaction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 47 publications
3
58
0
Order By: Relevance
“…Under NIR irradiation, photosensitizers can generate high singlet oxygen quantum yield, showing photothermal conversion efficiency and outstanding photoacoustic response–guided simultaneous PDT and PTT. Zhou et al reported the synthesis of polyaniline (PANI)‐loaded γ‐polyglutamic acid (γ‐PGA) nanogels for photoacoustic imaging–guided PTT of tumors …”
Section: Pharmacological Nanoparticles From Emulsion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under NIR irradiation, photosensitizers can generate high singlet oxygen quantum yield, showing photothermal conversion efficiency and outstanding photoacoustic response–guided simultaneous PDT and PTT. Zhou et al reported the synthesis of polyaniline (PANI)‐loaded γ‐polyglutamic acid (γ‐PGA) nanogels for photoacoustic imaging–guided PTT of tumors …”
Section: Pharmacological Nanoparticles From Emulsion Techniquesmentioning
confidence: 99%
“…Zhou et al reported the synthesis of polyaniline (PANI) loaded γpolyglutamic acid (γPGA) nanogels for photoacoustic imaging-guided PTT of tumors. [73] γPGA nanogels were first synthesized via a double emulsionsolvent evaporation process, followed by crosslinking with cystamine dihydrochloride. γPGA/ Cys nanogels were then used as nanoreactors for polymerizing aniline.…”
Section: Optical Imagingmentioning
confidence: 99%
“…However, the bad stability of the NIR dyes due to the photobleaching limits their application. Polyaniline (PANI) was the first reported organic polymer‐based photothermal agent with good stability and has been widely applied in photoacoustic imaging (PAI) and photothermal therapy (PTT) of tumors . PANI exists in two states, emeraldine base (EB) and emeraldine salt (ES), which can be interconverted through protonation and deprotonation reactions in different pH microenvironment .…”
Section: Introductionmentioning
confidence: 99%
“…PANI exists in two states, emeraldine base (EB) and emeraldine salt (ES), which can be interconverted through protonation and deprotonation reactions in different pH microenvironment . Under strongly acidic condition, the conversion of PANI from EB to ES state will cause its redshift absorption from visible to near‐infrared (NIR) region, promising for PAI and PTT . However, this conversion pH is considerably lower than that of tumor acidic microenvironment (5.4–7.0), which severely limits the application of PANI as a pH‐responsive agent for cancer theranostics .…”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of desirable nanoparticles (NPs) is an important task for developing efficient carriers in the biomedical field. Till now, NPs with distinct physicochemical properties including size, shape, composition, surface potential, and surface chemistry have been developed for various biomedical applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. When using nanomaterials in the biomedical field, it is critical to understand their interaction with cells [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%